Aspects of Indian Modernity: A Personal Perspective - Ramanan, Mohan (Miscelánea: A Journal of English and American Studies, 2006)
The paper attempts to delineate the contours of Indian modernity by showing that it is primarily colonial modernity which is a factor in the modern Indian nation taking shape. India is distinguised from Bharat which is the old name for the geographical space which is India. Bharat is traditional and India is modern. The paper shows that these categories need not be irreconcilable opposites, that the Indian way has been to effect a dynamic partnership of the past and the present, tradition and modernity, that if India does not do so now her future is at stake. The paper examines the growth of modernity in India through the nineteenth century and argues that to a large extent even this modernity and the stirrings of nationhood are informed by a spiritual attitude to life. The paper in short argues for a usable past which will preserve the best from tradition, select from it that which is useful and reject the dross so as to forge a future which is intimately linked with the past. Evolution, rather than revolution is the paper’s burden. That is the Indian way.